Multifunctional and Mechanically Robust Porous Diamond with Large Electroactive Surfaces via Electrically Conductive and Insulating Templates for 3D Electrode Applications. Issue 15 (29th April 2022) - Ashcheulov, Petr; Hák, Ondřej; Sedláková, Silvia; Taylor, Andrew; Baluchová, Simona; Schwarzová‐Pecková, Karolina; Davydova, Marina; Kopeček, Jaromír; Klimša, Ladislav; Vondráček, Martin; Honolka, Jan; Mortet, Vincent
Abstract: Highly functional 3D biological systems, which are ordinary in this physical world, suggest that traditional planar/flat materials when assembled into 3D variants, can deliver significantly higher levels of functionality and efficiency. Thanks to its set of unique properties, diamond has received significant recognition as the material of choice for a variety of functional platforms, however, implementation of diamond in real‐world applications has lagged behind alternative materials, which offer a greater degree of versatility. In this regard, for applications to benefit from diamond‐specific properties, approaches on fabrication of diamond beyond the common planar form in a practical and scalable manner are required today. Capitalizing on the ability to synthesize diamond over large areas, this study demonstrates fabrication of porous boron‐doped diamond (BDD) in freestanding form and on wafer‐compatible sizes. Porous BDD electrodes deliver robust electrochemical stability and exceptional electrical characteristics. Aiming to utilize the full potential of diamond properties, this study examines the impact of the BDD porous structure on the ability of electrodes to effectively remove organic pollutants from simulated wastewater and to provide enhanced sensitivity/selectivity of biologically active compounds. This study represents an important step in achieving diamond with extended functionality suitable for industrial/commercial scale implementation. Abstract : To advance the applicability of diamond in various platforms, this study investigates fabrication of large area 3D diamond structures. These porous diamond structures enable effective electrochemical treatment of water pollutants and sensing of biomolecules. Detailed characterization reveals that multifunctional characteristics originate from the enhanced structural dimensionality/porosity of diamond.